2018
DOI: 10.2147/dmso.s156858
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with adherence to diabetes care recommendations among children and adolescents with type 1 diabetes: a facility-based study in two urban diabetes clinics in Uganda

Abstract: PurposeThe purpose of this study was to determine the level of adherence and the factors associated with adherence to diabetes care recommendations among type 1 diabetic children and adolescents at two urban diabetes clinics in Kampala, Uganda.Research design and methodsA facility-based cross-sectional study was carried out among 200 children and adolescents with type 1 diabetes at two major diabetes clinics in Kampala. Caretakers of the children and adolescents were interviewed using pretested questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
1
19
0
2
Order By: Relevance
“…The rates of parents’ adherence to the NDT and BMPS exercises were similar, although the adherence rates for flexibility exercises was lower. This variability among the types of exercises is consistent with the variability reported among therapeutic modalities of medical treatments for children with chronic illnesses [8,21].…”
Section: Discussionsupporting
confidence: 84%
“…The rates of parents’ adherence to the NDT and BMPS exercises were similar, although the adherence rates for flexibility exercises was lower. This variability among the types of exercises is consistent with the variability reported among therapeutic modalities of medical treatments for children with chronic illnesses [8,21].…”
Section: Discussionsupporting
confidence: 84%
“…5 A facility-based study conducted in Uganda found that caregivers with low knowledge about diabetes did not adhere to diabetes care and management recommendations; however, this study did not consider dietary practices. 9 Another study conducted in Tanzanian caregivers reported a significant association between diabetes knowledge and glycated hemoglobin (HbA1c) levels. 10 In Kenya, another study established that the nutritional knowledge level among caregivers was significantly associated with the dietary practices of their children.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was suggested that reinforcing caregiver involvement in the children's diet could help improve adherence to dietary recommendations. 14,15 In Tanzania, a study reported a significant association between caregivers' knowledge of diabetes and HbA1c levels. 16 A parentbased nutrition educational intervention targeting mealtime behaviors reported a decrease in mean daily blood glucose levels among children with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%